Simplify Expressions

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

(-4p)^4

Oct 3rd, 2015

Hello!

(a*b)^d = a^d * b^d, (a*b*c)^d = a^d * b^d * c^d.

Here

(-4p)^4 = (-1*4*p)^4 = (-1)^4 * 4^4 * p^4 = 1*256*p^4 = 256*p^4.

Please ask if something is unclear.
Sep 16th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 3rd, 2015
...
Oct 3rd, 2015
Oct 21st, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer